“Diámetros mínimos y máximos de aprovechamiento en plantaciones de Tectona grandis L.f. (teca) en la Provincia del Guayas, 2020”. - Pilligua Macías, Joselyne Soraida (2020)
Teak is an exotic species, it is classified as an invasive plant since it does not have biological controllers or other species to compete with, so it occupies more land and available water, the diameters are developed depending on the site where it is found; That is to say that in humid areas it reaches a higher volume unlike in dry areas where they develop with little volume but with better durability and therefore obtain better quality. In this research, average calculations were made that revealed the best used diameter and the profit margin, surveys were applied to 11 teak sawmills located in the cantons of Balzar and El Empalme of the Province of Guayas and it was determined that the minimum diameter in which they begin to saw is from 12.09 to 15.92cm at this point the wood is exported in 20-foot containers in the form of a sharp edge obtaining a profitability of $ 360.09, contrary to the exportation in a carded form that its diameter begins from 22 up to 38.09 cm. Reaching a value of $ 379.74. The information obtained in this study can be used by individuals or companies that have an interest in investing in plantations and thus have a clearer idea of the economic profitability generated by this activity. Keywords: container, plantations, careada, sharp edge, use, diameter